Role Of Nasya In Ardita W.S.R To Facial Palsy: A Review - Divya, Aswal; Pretya, Juyal; Sharma, Rishu; Sharma , K K; Pravesh, Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Ardita is a medical condition causing the Vakratha [deviation] of Mukha ardha and leads to facial asymmetry and malfunction. It occurs due to aggravated Vata Dosha. It has been enumerated in Vata Nanatmaja Vyadhi by Acharya Charaka. Ashtang hridaya has said it as Ekayaam (loss of movement involving one half of the face or half of the body with half of the face). According to Acharya Charaka it affects Sharirardha while half side of the face is affected in Ardita according to Acharya Sushruta. It can be correlated to facial palsy in modern which carries similar complaints to Ardita of deviation of half of the face with sensory & motor impairment on the affected side. According to Acharya Charaka Nasya (Navana Nasya) is the specific treatment of Ardita. Sneha is considered as best Vatashamaka. Viscosity of Sneha increases the absorption of the drug by increasing the contact time to the nasal mucosa (Viryam Yavatadhivasat Nipatatcha) & lipophilic drugs have better absorptive capacity hence Navana Nasya is considered best.